PELATIHAN MODEL GROUP COUNSELING BAGI GURU PENDAMPING KHUSUS DI SEKOLAH DASAR INKLUSI - Dahlia Novarianing Asri; Novarianing Asri, Dahlia; Eko Hari Cahyono, Bambang; Sri Maruti , Endang (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Vocabulary learning for students with special needs, the accuracy of the selection of learning models and media greatly determines the success of learning objectives. Therefore, it is necessary to provide material and training for special assistant teachers of inclusive elementary schools in implementing the group counseling model with contemporary puppet media in vocabulary learning. The purpose of this training is to provide teachers with basic concepts related to vocabulary learning, group counseling models, and innovative learning media. In addition, it also aims to provide skills to special assistant teachers in Inclusive schools in Magetan Regency in implementing the group counseling model with contemporary puppet media to improve vocabulary mastery of students with special needs. The training activities were carried out in 3 stages, namely the material provision stage, practice in implementing the group counseling model with contemporary puppet media, and practice in implementing the group counseling model with contemporary puppet media in schools. The training method uses lecture methods, demonstrations, and direct practice in schools. The results of the training were that at the material provision stage, material was provided on vocabulary learning, group counseling, innovative learning media, and the group counseling model with contemporary puppet media. The group counseling model application training activities using contemporary puppet media were carried out through 3 activities, namely recreational activities, psychoeducation, and resolution. The evaluation results showed an increase in participants' understanding of the principles and basic techniques of group counseling, as well as an increase in their confidence in applying this model in the school environment. This activity is expected to support the creation of a more inclusive and responsive learning environment to students' needs. The recommendation from this activity is the need for further training and ongoing supervision to ensure the sustainability of group counseling practices by GPK in each school.